Optimization of coating thickness in a tangential fluidized bed - Ku Shaari, K.Z. (Trans Tech Publications Ltd, 2014)
The focal intention of this research was to investigate the factors influencing the coating thickness of urea granule by using modified biopolymer which performed in a tangential fluidized bed. The effects of inlet air temperature, disc rotation speed and spraying rate on coating thickness of urea granule were investigated. In this study, the results showed that the significant process parameters which effect the coating thickness was spraying rate (58.585), followed by disc rotation speed (21.579) and inlet air temperature (18.883). The optimized process parameters in this work were 400C for inlet air temperature, 40 rpm for disc rotation speed and 2 rpm for spraying rate. The confirmation run for this work had verified the conclusion from the variance analysis. Â© 2014 Trans Tech Publications, Switzerland.